A comparison of linear and non-linear strategies for energy harvesting from mechanical vibrations - Andò, Bruno; Baglio, Salvatore; Marletta, Vincenzo; Bulsara, Adi R. (Frontiers in Physics, 2023)
Energy Harvesting strategies together with the improvement of electronics and the progressive reduction of power requirements have been widely recognized as fundamental to enable self-powered (or autonomous) devices. Among all the potential energy sources, kinetic energy stemming from mechanical vibrations has been particularly extensively investigated for EH purposes due to its characteristics of heterogeneity and ubiquity. To exploit such energy sources, a suitable coupling mechanism to convert vibrations into electric charge is required; it must take into account the wide frequency bandwidth of mechanical vibrations as encountered in everyday scenarios. This review offers an overview of linear vs. non-linear strategies for EH, with a specific focus on different approaches to implement efficient coupling mechanisms; the performances of the specific solutions covered in this work are discussed.